Enhancement of seed germination of wild plant species through priming - Nayyef, Alaa; Merritt, David; Turner, Shane; Pritchard, Deborah (2018)
Desertification is a serious problem affecting the survival of many plants endemic to arid regions. Revegetation is difficult because it is widely influenced by extreme climatic factors, disturbance, limited revegetation technology and importantly a lack of understanding of the biology and ecology of native plant species. Seeds are central to the revegetation of degraded lands, but poor seedling establishment limits our capacity to restore diverse plant communities. Priming is an effective method to enhance seed germination. The purpose of this study is to enhance seed germination of species adapted to arid regions using priming technology and hence assist in arid land restoration. A seed priming experiment was conducted on native plant species (Poaceae) from the Pilbara region (northern Western Australia) in an attempt to improve germination percentage and the seeds resistance to water stress. Some combinations of priming treatments significantly increased germination percentage for two Poaceae species (Cymbopogon obtectus, Eriachne mucronata) under water stress. Priming has a positive effect on germination parameters such as germination percentage and speed for seeds under certain water stress; however, this positive effect decreases when water stress is high (-1.0 MPa). This study assists in better understanding how to improve germination of native species from the arid Pilbara which will improve the success of revegetation programs.